Parabrachial opioidergic projections to preoptic hypothalamus mediate behavioral and physiological thermal defenses - Norris, Aaron J (eLife, 2021)
Maintaining stable body temperature through environmental thermal stressors requires detection of temperature changes, relay of information, and coordination of physiological and behavioral responses. Studies have implicated areas in the preoptic area of the hypothalamus (POA) and the parabrachial nucleus (PBN) as nodes in the thermosensory neural circuitry and indicate that the opioid system within the POA is vital in regulating body temperature. In the present study we identify neurons projecting to the POA from PBN expressing the opioid peptides dynorphin and enkephalin. Using mouse models, we determine that warm-activated PBN neuronal populations overlap with both prodynorphin (Pdyn) and proenkephalin (Penk) expressing PBN populations. Here we report that in the PBN Prodynorphin (Pdyn) and Proenkephalin (Penk) mRNA expressing neurons are partially overlapping subsets of a glutamatergic population expressing Solute carrier family 17 (Slc17a6) (VGLUT2). Using optogenetic approaches we selectively activate projections in the POA from PBN Pdyn, Penk, and VGLUT2 expressing neurons. Our findings demonstrate that Pdyn, Penk, and VGLUT2 expressing PBN neurons are critical for physiological and behavioral heat defense.